The Role of Teachers in Forming a Superior Generation in the Digital Era - Grace Tan Mei Ling; Syafiq (Outline Publisher, 2024)
The role of teachers in shaping a superior generation in the digital era is very important considering the rapid development of technology that affects all aspects of life, including education. This study aims to explore the role of teachers in utilizing technology to create innovative, flexible, and relevant learning to the needs of students in the 21st century. The method used in this study is mixed methods, by combining qualitative approaches through in-depth interviews and quantitative through questionnaires. The results of the study show that most teachers have good digital literacy and have integrated technology into the learning process. However, the challenges faced include limited training time, uneven access to technology, and gaps in supervision of technology use at home. Technology-based learning can improve students' skills such as collaboration, communication, and problem solving. In addition, this study emphasizes the importance of the role of teachers in instilling digital ethics and overcoming social challenges posed by technology. Collaboration between teachers, parents, and the government is needed to create a learning environment that supports the formation of a superior generation that is able to face global challenges in the digital era.